1999
DOI: 10.1007/s003600050222
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal changes in blood composition of the free-living Egyptian fruit bat ( Rousettus aegyptiacus )

Abstract: We studied the blood profile of the free-living fruit bat (Rousettus aegyptiacus) during the beginning of the activity period (around various feeding trees) and upon return to the day roost during 1994-1995. Results of the present study suggest that during winter and early spring bats are characterized by a poor physical and physiological state as reflected in the blood profile, revealing elevated urea and uric acid concentrations. It was found that at the end of the resting phase, R. aegyptiacus was in a mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
19
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
8
19
1
1
Order By: Relevance
“…Indeed, some individuals exhibited intermediate values during the plateau phase, but we attribute these to instability in the measurements given that overestimation and underestimation of the expected plateau value occur to the same extent. In general, our results are in accord with those of Korine and colleagues (Korine et al, 1999b) who found that blood glucose and triglyceride levels are negatively correlated in postprandial Egyptian fruit bats indicating that exogenous glucose is the prime energy source during their active phase at night, and endogenous lipids are the prime energy source during their daytime rest phase.…”
supporting
confidence: 93%
“…Indeed, some individuals exhibited intermediate values during the plateau phase, but we attribute these to instability in the measurements given that overestimation and underestimation of the expected plateau value occur to the same extent. In general, our results are in accord with those of Korine and colleagues (Korine et al, 1999b) who found that blood glucose and triglyceride levels are negatively correlated in postprandial Egyptian fruit bats indicating that exogenous glucose is the prime energy source during their active phase at night, and endogenous lipids are the prime energy source during their daytime rest phase.…”
supporting
confidence: 93%
“…The lack of fluctuations in blood glucose levels throughout the year is a good indicator of the animals' physiological state (Korine et al 1999), and corroborates the pattern found in other species of fruit bats ), blood-eating bats (Freitas et al 2006;Gomes 2008), and insect-eating bats (Srivastava and Krishna 2008;Freitas et al 2010).…”
Section: Discussionsupporting
confidence: 57%
“…Seasonal changes in hematology have been recorded in birds [1,5,9,17,20,27], bears [8], deer [14], bats [12] and fish [4]. However, there have been few reports of seasonal changes of hematological values for marine mammals [26].…”
mentioning
confidence: 99%